Urban environment, health, and equity - Elodie Eiffener; Andrei Pyko; Östen Axelsson; Rachel Murekatete; Anne-Sophie Merritt; Antonios Georgelis; Olena Gruzieva; Mare Lõhmus; Niklas Andersson; Kristina Eneroth; Mikael Ögren; Marco Pretto; et al. (Environmental Epidemiology, 2026)
Background: Urban residents are exposed to multiple environmental stressors, but robust evidence on inequities in environmental exposure and associated health and well-being outcomes remains limited. Aim: To assess inequities in residential exposure to air pollution (PM 2.5 , PM 10 , and NO 2 ), traffic noise (road, railway, and aircraft) and greenness (NDVI within 300 m), and to characterize associations with self-reported symptoms and annoyances. Methods: The study population comprised 46,282 adults (18–84 years) residing in Stockholm County, Sweden, who responded to the Swedish National Environmental Health Survey 2023. Residential exposure (dichotomized) was based on geocoded address coordinates and stratified by socioeconomic status (SES) and building type. Logistic regression estimated adjusted odds ratios (OR) with 95% confidence intervals (95% CI) and tested effect modification via interaction terms. Results: Apartment residents were more often exposed to air pollution and noise and had less surrounding greenness than house residents. SES-stratified analyses revealed exposure-specific patterns, but no consistent overall trends. Air pollution exposure was associated with perceived poor outdoor air quality (NO 2 : OR = 3.22; 95% CI = 2.75–3.79), traffic noise with, for example, high noise annoyance (road traffic: OR = 4.59; 95% CI = 4.02–5.26), and greenness, for example, with lower perceived indoor heat stress during summer (OR = 0.83; 95% CI = 0.79–0.88). Self-reported health and well-being varied by SES and building type. Conclusions: Our study reveals concentrated environmental stressors in dense residential areas and highlights multidimensional environmental inequities. Environmental exposure was associated with self-perceived health and well-being, underscoring the need for integrated, system-based policies, such as One Health, to promote sustainable urban well-being.